PERAN GURU BAHASA DAN SASTRA INDONESIA DALAM PEMBELAJARAN YANG INOVATIF - Rukni Setyawati (Buana Bastra, 2015)
Abstract Teacher as an instructor while educators must be aware of the changes and demands of an increasingly complex task with the impact thereof. In teaching and learning activities, teachers should adapt to demands and needs of the students. The purpose of learning so that the direction and maintenance of appropriate levels of education can be the targets set by the government that is contained in the curriculum in 2013. Curriculum 2013 has been rolling for a year of learning emphasis on attitude (the attitude of the spiritual and social attitudes), which was followed by aspects of skills and cognitive aspects. It is intended that learners can soon become an honorable man, responsible, and independent. In the 2013 curriculum students are required to skilled, creative, and can berinovatif in receiving classroom. The role of learners in the curriculum 2013 was passive, not just talk mendengarkn teachers, but learners claimed an active role in the learning process. Similarly, the teacher in the learning process should be able to face learners using the strategies, methods, and the right approach, so that students are not saturated and will be motivated to follow the learning process. Referring to the framework of 21st century competencies learning process should be able to create learning exercises which allow educators to collaborate, enabling learners to learn relevant to the context of the world. Therefore, the learning process should be able to give birth learners innovative and creative. for mature and intelligent students in order to develop their potential optimally. Key Words: teacher, strategies, curriculum, 2013, innovation.